KEPEMIMPINAN KETUA YAYASAN BERDASARKAN KECERDASAN EMOSI (EQ)DI LEMBAGA PENDIDIKAN ASY SYAMIL BONTANG KALIMANTAN TIMUR TAHUN 2024 - Mustaghfiroh, Mustaghfiroh (UNISAN JURNAL, 2025)
This study discusses the role of emotional intelligence (EQ) in the leadership of the Foundation Chair at Asy Syamil Educational Institution in Bontang, East Kalimantan, in 2024. Emotional intelligence is considered an important factor in determining the effectiveness of a leader, especially in an educational context. In this study, the author analyzes how EQ can influence decision-making, interactions with staff and students, and the ability to build a positive environment within the educational institution. Data was collected through interviews, observations, and questionnaires involving foundation management, teachers, and students. The research findings indicate that leaders with high emotional intelligence are able to enhance work motivation, create better communication, and reduce conflicts in the school environment. These findings are expected to provide insights for other educational institutions regarding the importance of applying EQ in leadership. Keywords: leadership, emotional intelligence, education, effectiveness, Asy Syamil Educational Institution.